On the use of non-linear TVD filters in finite-volume simulations - Bodnár, Tomáš (Proceedings of the Conference Algoritmy, 2015)
This paper aims to demonstrate the e®ect of digital ¯ltering on solution of advection dominated phenomena using ¯nite-volume methods. The non-oscillatory post-processing procedure is based on the simple ¯lter presented in [4]. Some simple one-dimensional tests are presented to show the efficiency of this stabilization technique. Further references are given to the authors papers using this technique as well as to other literature discussing this or other filtering techniques applicable for solution of some other CFD problems.